Quantifying attributes of boring bivalve populations in corals using micro-computed tomography - Kramer, Netanel; Amit, Tal; Gavrieli, Noga; Gross, Maya; Wangpraseurt, Daniel; Loya, Yossi (Frontiers in Marine Science, 2024)
Bioerosion plays a crucial factor in shaping the structure and function of coral reef ecosystems, with bioeroders actively altering both the physical and ecological dynamics of coral substrates. Despite their importance, studying internal bioeroders in corals presents significant challenges owing to their cryptic nature within the skeletal structures. Additionally, invasive methods are often required to reveal the subtle and microscopic bioerosive alterations they induce in calcium carbonate substrates. Here, we demonstrate the effectiveness of high-resolution micro-computed tomography (μCT) in quantifying the abundance, size, distribution, and growth directions of coral bioeroders such as cryptic calcareous bivalves in the northern Red Sea. We scanned three coral species inhabited by bioeroders, followed by the utilization of three-dimensional image analysis software to identify, count, and measure each bivalve within the coral skeleton, along with quantifying boring cavity volumes. We revealed that μCT captures small boring cavities (< 1mm), providing more accurate abundance estimates of live and dead boring bivalves than the skeleton decalcification technique, with the added benefits of being rapid and non-destructive in contrast to traditional methods. Furthermore, measurements of empty cavity volumes enabled the estimations of the contribution of bioeroders to the overall coral skeletal porosity. Overall, our study highlights μCT as a practical and effective tool for studying cryptic coral bioeroders, providing novel ecological insights into bioeroder population ecology and coral-bioeroder interactions.